Assessing the creditworthiness of construction enterprises by different methods - A. Shkileva, Anna (International Journal of Engineering and Technology, 2018)
The article presents an assessment of the creditworthiness of a construction company with the help of three methods: the classical method of rating the enterprise, the methodology of R.S. Sayfullin and G.G. Kadykov, the methodology of the PJSC "Savings Bank of Russia". A comparison of these methods was carried out using the example of "Mostostroy-11".Â Â